Venous superdrainage using superficial circumflex iliac vein in deep circumflex iliac artery perforator flap with iliac crest for oromandibular reconstruction. Issue 1 (January 2022) - Wu, W.-J.; Zheng, L.; Zhang, J.; Lv, X.-M.; Huang, M.-W.; Shi, Y.; Liu, S.-M.
Abstract: The deep circumflex iliac artery perforator flap with iliac crest (DCIAPF) is considered a favourable single-flap option for oromandibular reconstruction. The aim of this study was to evaluate the effectiveness of venous superdrainage using the superficial circumflex iliac vein (SCIV) in the DCIAPF for oromandibular reconstruction. The data of 22 patients (12 female, 10 male) aged 10–76 years (median 53 years) who underwent simultaneous oromandibular reconstruction with a DCIAPF were reviewed retrospectively. Eleven patients received the DCIAPF with SCIV for superdrainage (group A) and another 11 patients received the conventional single-pedicled DCIAPF flap (group B). No flap loss occurred in either group. Venous congestion due to relative venous insufficiency was significantly more frequent in group B ( P = 0.045). There was no significant difference in the incidence of partial flap necrosis and wound dehiscence, or in the total operation time between the two groups. Superdrainage using the SCIV has the potential to reduce the incidence of venous congestion due to relative venous insufficiency in DCIAPF used for oromandibular reconstruction.